CRITICAL SUCCESS FACTORS FOR ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION: EVIDENCE FROM MANUFACTURING COMPANIES - Yana Hadiyat; Budi Septiawan; Annisa Adha (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Not all manufacturing companies are successful in implementing an integrated Accounting Information System (AIS), it requires the right combination of technology and humans as the main drivers. This research explored the relationship between organizational commitment from AIS users, knowledge of accounting managers, and data quality on the success of AIS implementation in manufacturing companies. A quantitative approach used the SEM-PLS method on 50 manufacturing companies in Indonesia. Meanwhile, the research results stated that data quality and knowledge of accounting managers had a positive and significant effect on the success of AIS implementation, while organizational commitment did not have a significant effect. This research implied that manufacturing companies could emphasize quality data and increase the knowledge of their managers to provide value to the organization through AIS.